The Effect of Linearity of Teachers' Educational Background on Learning Motivation at SMAN 1 Ngantang - Adelia Adelia; Agus Tinus; Kuncahyono Kuncahyono (MASI Mandiri Edukasi, 2026)
This study aims to: (1) Analyze the linear influence of teacher educational background on student learning motivation at SMAN 1 Ngantang. (2) Determine the significant differences in student learning motivation taught by teachers with linear and non-linear educational backgrounds at SMAN 1 Ngantang. This study uses a quantitative approach with a correlational design. This approach was chosen to test the linear influence between teacher educational background on student learning motivation in Senior High School (SMA). This study was conducted at State Senior High School (SMA) 1 Ngantang, located in Ngantang District, Malang Regency, East Java. To measure students' learning motivation and teachers' educational backgrounds, this study will use an existing questionnaire validated in previous similar studies. The use of instruments that have been tested for validity and reliability enables more accurate data collection and reduces the potential for measurement bias. The results of the study show that the regression equation Y = 84.194 + 0.129X indicates that the linearity of teacher educational background has a positive relationship with student learning motivation. Based on the t-test results, a significance value of 0.462 > 0.05 was obtained, thus concluding that the linearity of teacher educational background does not significantly influence student learning motivation. The results of the coefficient of determination (R²) test showed an R-square value of 0.022, which means that the linearity of teacher educational background only contributes 2.2% to student learning motivation, while the remaining 97.8% is influenced by factors outside the research variables.